Learning about “wicked” problems in the Global South. Creating a film-based learning environment with “Visual Problem Appraisal” - Witteveen, Loes; Lie, Rico (MedieKultur: Journal of media and communication research, 2012)
The current complexity of sustainable development in the Global South calls for the design of learning strategies that can deal with this complexity. One such innovative learning strategy, called Visual Problem Appraisal (VPA), is highlighted in this article. The strategy is termed visual as it creates a learning environment that is film-based. VPA enhances the analysis of complex issues, and facilitates stakeholder dialogue and action planning. The strategy is used in workshops dealing with problem analysis and policy design, and involves the participants “meeting” stakeholders through filmed narratives. The article demonstrates the value of using film in multi stakeholder learning environments addressing issues concerning sustainable development.